" We will change between the movement of history and the religious concept of society "Islam as a model - Al Harthy, Noura Ahmed Hamed (Journal of Humanities & Social Sciences, 2018)
This research deals with the concept of change in the light of the concepts of history movement and the religious concept of society in the period of Islam, by addressing the issues of articulation formed a year of the life of the Arab society in the era of the first letter, The main issues discussed in this paper are: Dissolution of the concept of traditional leadership prior to the dawn of Islam, the religious shift from the worship of multiple gods to the doctrine of monotheism, the societal shift towards justice and equality, and the rejection of slavery and social differences. The research tackles these issues from a methodological perspective. The application of the Qur’anic text and the Prophet’s biography, while employing the heritage for the necessities of change and placing it in the context of some of the reality we are living today.